2003
DOI: 10.1080/10473289.2003.10466192
|View full text |Cite
|
Sign up to set email alerts
|

Variables Affecting Emissions of PCDD/Fs from Uncontrolled Combustion of Household Waste in Barrels

Abstract: The uncontrolled burning of household waste in barrels has recently been implicated as a major source of airborne emissions of polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs). A detailed, systematic study to understand the variables affecting emissions of PCDD/Fs from burn barrels was performed. The waste composition, fullness of the barrel, and the combustion conditions within the barrel all contribute significantly to determining the emissions of PCDD/Fs from burn barrels. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 4 publications
7
25
1
Order By: Relevance
“…These hypotheses are supported by the results of Wevers et al [14] where the burnout stage of a pine/hardwood mixture exhibited a greater tendency for dioxin emission than the preceding ignition and flaming stages. These results were further confirmed in the burning of household refuse by Lemiuex et al [15]. Other recent studies have shown that, the presence of the preservative CCA in pine, dramatically increased the ash dioxin concentration in the ash under fire conditions [16].…”
Section: Introductionsupporting
confidence: 75%
“…These hypotheses are supported by the results of Wevers et al [14] where the burnout stage of a pine/hardwood mixture exhibited a greater tendency for dioxin emission than the preceding ignition and flaming stages. These results were further confirmed in the burning of household refuse by Lemiuex et al [15]. Other recent studies have shown that, the presence of the preservative CCA in pine, dramatically increased the ash dioxin concentration in the ash under fire conditions [16].…”
Section: Introductionsupporting
confidence: 75%
“…13 For unregulated, open burning of power cable scrap, Bremmer et al 13 used estimates of 500 ng I-TEQ/kg for inventories in the Netherlands. However, given the signifi cantly higher PCDD/PCDF emission factors and variability obtained during open, uncontrolled burning of household waste 14,15 compared to well-controlled commercial municipal solid waste incinerators, it is not clear how relevant these reported values from commercial activities are to the open burning of e-waste.…”
Section: Introductionmentioning
confidence: 78%
“…These two values fall within the range of values reported for tests of uncontrolled barrel burning of residential waste. 15 The high relative standard deviation (RSD = 98%) between the two samples is not unexpected for these analytes in combustion tests involving relatively small sample sizes. The emissions for the insulated wires were 12 400, 18 100, and 5400 ng TEQ/kg (RSD = 50%).…”
Section: Pxdd/pxdf Measurementsmentioning
confidence: 94%
See 1 more Smart Citation
“…[17] Such investigations emphasize the importance of PCDD/Fs environmental monitoring. Combustion processes (open burning) on unsanitary landfills are incidents which are often carried out due to effective volume reduction, [18] with highly irregular duration and occurrence, most often without permission and, for this reason, not well documented.…”
Section: Introductionmentioning
confidence: 99%